The Influence of CaF2 Doping on the Sintering Behavior and Microwave Dielectric Properties of CaO-B2O3-SiO2 Glass-Ceramics for LTCC Applications - Chao Dong; Hua Wang; Tingnan Yan; Jianwei Zhao; Jiwen Xu; Dawei Wang (Crystals, 2023)
With the rapid development of microelectronic information technology, microelectronic packaging has higher requirements in terms of integration density, signal transmission speed, and passive component integration. Low temperature co-fired ceramics (LTCC) exhibit excellent dielectric properties and low temperature sintering properties, which meets the above-mentioned requirements. This work investigates the effects of CaF2 doping (0–16 mol%) on the glass structure, sintering behavior, crystallization, microstructure, and microwave dielectric properties of the CaO-B2O3-SiO2 (CBS) glass-ceramic system. Glass-ceramics were prepared using the conventional melting and quenching method. The physical and chemical properties of the glass-ceramics were analyzed using various techniques including TMA, SDT, FTIR, XRD, SEM, and a network analyzer. The results indicate that CaF2 doping can effectively reduce the sintering temperature and softening temperature of CBS ceramics. It also substantially improves the densification, dielectric, and mechanical properties. The appropriate amount of CaF2-doped CBS glass-ceramics can be sintered below 800 °C with a low dielectric constant and loss at high frequency (εr < 6, tanδ < 0.02 @ 10~13 GHz). Specifically, 8 mol% CaF2 doped CBS glass-ceramics sintered at 790 °C exhibit excellent microwave dielectric and thermal properties, with εr ~ 5.92 @ 11.4 GHz, tanδ ~ 1.59 × 10−3, CTE ~ 7.76 × 10−6/°C, λ ~ 2.17 W/(m·k), which are attractive for LTCC applications.